KEDUDUKAN PENYIDIK PEGAWAI NEGERI SIPIL (PPNS) DALAM SISTEM PERADILAN PIDANA - Adi Kusuma, Made; Darmawan, Ni Ketut Supasti (Kertha Wicara : Journal Ilmu Hukum, 2013)
The criminal justice system in Indonesia consists of components of constabulary,prosecutors, judiciary and penitentiary, as well as components of advocate.Constabulary component have a duty to conduct an investigation of a crime. However,based on the Indonesian book of the law Criminal Code (KUHAP), it says there is onemore component in charge of the investigation, namely the Civil Servant investigators,so it needs to be explained further how the position of the Civil Servant in theIndonesian criminal justice system.
Keywords: Criminal Justice System, Civil Servant Investigator, Investigation, Indonesian Book Of Law Criminal Code (KUHAP)